The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1080/00016340601110747
|View full text |Cite
|
Sign up to set email alerts
|

Early random capillary glucose level screening and multidisciplinary antenatal teamwork to improve outcome in gestational diabetes mellitus

Abstract: Early non-fasting random universal screening and multidisciplinary antenatal teamwork intervention seems to be favourable, with low rates of excessive fetal growth, instrumental vaginal delivery and caesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
3
12
1
Order By: Relevance
“…Sweden is considered to have a rather low prevalence of GDM (i.e., around 1.4%) [12]. Using the current screening methods and thresholds in Sweden, this study confirmed this level of GDM.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Sweden is considered to have a rather low prevalence of GDM (i.e., around 1.4%) [12]. Using the current screening methods and thresholds in Sweden, this study confirmed this level of GDM.…”
Section: Discussionsupporting
confidence: 74%
“…Applying the diagnostic criteria of the International Association of Diabetes and Pregnancy Study Group (IADPSG) and the international multi-centre HAPO has demonstrated significant variability of prevalences of GDM among participating countries and even among participating study centres within the same country [11]. From a global perspective, Sweden is considered a low risk country for GDM with an annual prevalence of 1 to 2.6% of this pregnancy-related disorder [12,13]. There is, however, no international consensus regarding how women should be screened for GDM, whether screening should be undertaken universally, or whether women who present risk factors [14] should undergo screening, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…No agreement on a single threshold glucose value exists, above which maternal or perinatal complications are markedly increased (14). Previous studies (10, 15, 16) and the present study show that the degree of the severity of GDM, as indicated by high glucose values and the need of insulin treatment, clearly influences the complication rates. In our study, the diet‐treated GDM women had a low incidence of fetal macrosomia comparable to that of the non‐diabetic controls, whereas GDM patients needing insulin in addition to their diet showed a significantly higher incidence of fetal macrosomia than the controls or the diet‐treated GDM women.…”
Section: Discussioncontrasting
confidence: 52%
“…GDM is associated with other pregnancy complications and is an indicator of future development of diabetes mellitus type 2 [2]. In Sweden, the prevalence of GDM is reported in 1.2 - 2.3% of the pregnant women [3-6]. Since the 1990s, Sweden has officially adopted the European recommendation of selective screening for GDM [7].…”
Section: Introductionmentioning
confidence: 99%